Kepemimpinan Kepala Sekolah Dalam Penerapan Deep Learning Di Smk Citra Bangsa Mandiri - Sari, Prisillia Mustika; Hanif, Muh. (Universitas Pakuan, 2025)
Deep learning has become a strategic necessity in vocational education as it emphasizes the ability to understand, reflect, and apply knowledge contextually according to 21st-century workplace demands. This study aimed to analyze the role of principal leadership in implementing deep learning at SMK Citra Bangsa Mandiri Purwokerto, which has six areas of expertise. Using a mixed methods design with an explanatory sequential model, this research involved 30 informants consisting of principals, vice principals, teachers from various concentrations, administrative staff, and student representatives. Data were collected through Likert scale-based questionnaires, semi-structured interviews, non-participatory observations, and documentation. Quantitative analysis used descriptive statistics and simple regression, while qualitative analysis employed thematic coding techniques. The results showed that transformational, instructional, distributive, and charismatic leadership played significant roles in implementing deep learning encompassing pedagogical practices, learning environments, digital utilization, and learning partnerships. Findings indicated that visionary and collaborative leadership created a learning ecosystem supporting meaningful, mindful, and joyful experiences while developing eight graduate profile dimensions. This research provided theoretical and practical contributions to developing vocational education leadership relevant to 21st-century competency needs.